In-situ residual stress analysis during annealing treatments using neutron diffraction in combination with a novel furnace design. (15th November 2016) - Aba-Perea, P.E.; Pirling, T.; Preuss, M.
Abstract: A method for in-situ monitoring of residual strain/stress evolution during annealing treatments has been developed using a new induction heating setup designed for neutron strain-scanning instruments. First, time-of-flight neutron diffraction was used for determining the location and level of maximum residual stresses induced by quenching in disc shape samples of Ni-base superalloy Inconel 718. These were found to be in the centre of the samples being 700 MPa in tension in radial/hoop directions and − 300 MPa in axial direction. Subsequently, an in-situ annealing experiment was undertaken at 750 °C for 8 h in order to monitor the d-spacing evolution in this particular location in the three principal directions and in an attached stress-free sample. The measurements revealed that most stress relaxation occurs during the heating stage as a result of a combination of plasticity and early stage creep relaxation. During the isothermal stage the d-spacing changes measured in the stressed sample were dominated by the evolution of the stress-free d-spacing resulting in only very limited further stress relaxation. Ex-situ measurements after annealing confirmed the in-situ observations at the 8 h mark of 60% residual stress reduction validating the in-situ experimental protocol. Graphical abstract: Highlights: A novel sample environment for in-situ analysis of stress relaxation during annealing treatments was developed. The stress free d-spacing changes significantly during the heat treatment because of microstructural evolution. The stress relaxation in Inconel 718 during ageing results from plasticity and creep mechanisms. Ageing treatment at 750 °C/8 h of water quenched Inconel 718 relaxes residual stresses by approximately 60%.